Puzzle Sticks as a Medium for Number Recognition in Children with Learning Disabilities: Stik Puzzle sebagai Media Pengenalan Angka pada Anak Hambatan Belajar - Sunarti, Sunarti; Chamidah, Atien Nur (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Early numeracy is fundamental for children’s cognitive development, yet children with learning disabilities often struggle to recognize numbers, leading to long-term academic challenges. Specific Background: At Bengalon 1 State Kindergarten, several children demonstrated difficulties in associating numerical symbols with quantities, highlighting the need for low-cost, multisensory interventions. Knowledge gap: Previous studies on puzzles largely emphasized general cognitive or motor aspects, with limited focus on number recognition for children with learning disabilities. Aim: This study explored the use of puzzle sticks to support number recognition in children with learning disabilities through Classroom Action Research (two cycles of planning, action, observation, and reflection). Results: Findings showed substantial improvement. Initially, children scored between 33%–44% (“Not Yet Appeared” or “Appears with Guidance”). In Cycle I, scores increased to 41%–58% but remained below the 75% success threshold. In Cycle II, all children reached 75%–91%, meeting mastery criteria. Novelty: The study demonstrates the specific application of puzzle sticks as a structured numeracy intervention for children with learning disabilities. Implications: Puzzle sticks are affordable, engaging, and adaptable for inclusive classrooms, offering practical guidance for early childhood teachers. Further studies should examine long-term retention and multimodal puzzle designs. Highlight Puzzle sticks improved number recognition among children with learning disabilities. Multisensory activities increased engagement, accuracy, and independence in learning. Affordable and adaptable puzzle sticks provide practical tools for inclusive classrooms. Keywords Number Recognition, Puzzle Sticks, Learning Disabilities, Early Childhood Education, Inclusive Classroom